Respuesta :
Answer:
[tex]x=\frac{y-b}m[/tex]
Step-by-step explanation:
We subtract b from both sides.
[tex]y-b = mx[/tex]
We divide both sides by m (as long as [tex]m\ne0[/tex]) and read right to left.
[tex]x= \frac{y-b}m[/tex]
Answer:
[tex]x=\frac{y-b}{m}[/tex]
Step-by-step explanation:
[tex]\mathrm{Switch\:sides}[/tex]
[tex]mx+b=y[/tex]
[tex]\mathrm{Subtract\:}b\mathrm{\:from\:both\:sides}[/tex]
[tex]mx+b-b=y-b[/tex]
[tex]\mathrm{Simplify}[/tex]
[tex]mx=y-b[/tex]
[tex]\mathrm{Divide\:both\:sides\:by\:}m;\quad \:m\ne \:0[/tex]
[tex]\frac{mx}{m}=\frac{y}{m}-\frac{b}{m};\quad \:m\ne \:0[/tex]
[tex]\mathrm{Simplify}[/tex]
[tex]x=\frac{y-b}{m};\quad \:m\ne \:0[/tex]
[RevyBreeze]